Decision Support System for Determining Contract Employees to Become Permanent Employees at PT. Timbang Deli with Analytical Hierarchy Process (AHP) Method - Dewi Lestari (International Journal of Basic and Applied Science, 2021)
Contract employees in a company are hired to help with the work in the company but it is not unusual to ascertain how the work continues in the company. Determination of contract employees to become permanent employees at PT. Timbang deli, it still looks less precise and takes time, because the assessment and calculation of the results of the determination of contract employees to become employees are still carried out in stages such as file selection, oral tests or written tests, interviews and so on , so that the possibility of errors in the final results from determining contract employees to permanent employees often does not meet the criteria required by the company and hampers the company's performance. This study aims to design a Decision Support System Determining contract employees to be permanent employees who can assist the company in choosing the right employees using Visual Basic 2008 programming language. The results of this study build a decision support system using the method of analytical hierarchy process (AHP) to calculate the results in determining contract employees to become permanent employees and using UML to design programs.